High-density lipoproteins and non-alcoholic fatty liver disease - Hoekstra, Menno; Van Eck, Miranda (Atherosclerosis plus, 2023)
Non-alcoholic fatty liver disease (NAFLD), a high incidence liver pathology, is associated with a ∼1.5-fold higher cardiovascular disease risk. This phenomenon is generally attributed to the NAFLD-associated increase in circulating levels of pro-atherogenic apolipoprotein B100-containing small dense low-density lipoprotein and plasma hypertriglyceridemia. However, also a significant reduction in cholesterol transported by anti-atherogenic high-density lipoproteins (HDL) is frequently observed in subjects suffering from NAFLD as compared to unaffected people. In this review, we summarize data regarding the relationship between NAFLD and plasma HDL-cholesterol levels, with a special focus on highlighting potential causality between the NAFLD pathology and changes in HDL metabolism. Publications in PUBMED describing the relationship between HDL levels and NAFLD susceptibility and/or disease severity, either in human clinical settings or genetically-modified mouse models, were critically reviewed for subsequent inclusion in this manuscript. Furthermore, relevant literature describing effects on lipid loading in cultured hepatocytes of models with genetic alterations related to HDL metabolism have been summarized. Although in vitro observations suggest causality between HDL formation by hepatocytes and protection against NAFLD-like lipid accumulation, current literature remains inconclusive on whether relative HDL deficiency is actually driving the development of fatty liver disease in humans. In light of the current obesity pandemic and the associated marked rise in NAFLD incidence, it is of clear scientific and societal interest to gain further insight into the relationship between HDL-cholesterol levels and fatty liver development to potentially uncover the therapeutic potential of pharmacological HDL level and/or function modulation. •Non-alcoholic fatty liver disease (NAFLD) is associated with reduced HDL levels.•The cholesterol efflux capacity of HDL particles is impaired in NAFLD patients.•NAFLD is associated with marked changes in the HDL particle lipidome and proteome.•HDL production by cultured hepatocytes protects against lipid accumulation.•Whether low HDL levels predispose to NAFLD development in vivo remains uncertain.